FAMILY VIOLENCE IN MODERN UZBEKISTAN - Mukhtorjanovna, Latipova Nodira; Khabibovna, Ganieva Marifat; Asilbekovn, Abduvalieva Mumtozkhon; kizi, Ziyaeva Holida Omonkul (International Journal of Psychosocial Rehabilitation, 2020)
This article covers the problem of violence, both domestic and violence against women and children. The essential characteristics of the concepts of “violence”, “domestic violence”, “child abuse”, “domestic violence”, as well as the types of violence are analyzed. Analyzed a sociological study "The attitude of young people to violence", conducted among students. Considered preventive measures to prevent cruel and negligent treatment of children.